The collateral consequences of sex offender management policies: views from professionals - McCall, Corey (International journal of offender therapy and comparative criminology, 2018)
In this study, the perceptions of community corrections professionals and clinical specialists toward the collateral consequences of current sex offender management policies were explored and contrasted. In addition, potential influencing factors of these perceptions were examined. Results indicate high levels of belief that sex offenders experience a variety of collateral consequences upon reentry; however, community corrections professionals are significantly less likely to believe that sex offenders experience collateral consequences than clinical specialists. Furthermore, few demographic variables were found to significantly influence the perceptions of the sample. Implications for the management of sex offenders are discussed.